Hervé Niquet and Le Concert Spirituel perform Handel's Music for the Royal Fireworks At Chambord Castle - Charpentier, Marc-Antoine 1643-1704; Charpentier, Marc-Antoine 1643-1704; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759; Handel, George Frideric 1685-1759 (Prisemdia - Domaine National de Chambord, 2016)
At the inauguration of the 2016 Chambord festival, a crowd of over 4,000 was treated to a grandiose celebration of fireworks, both literal and musical in front of the Castle! Under the direction of their founder Hervé Niquet, the 70-some trumpeters, oboists, bassoonists, and other instrumentalists of Le Concert Spirituel turn their trademark historical precision and abundant energy to Baroque masterpieces by Handel, including his Music for the Royal Fireworks and his three Water Music suites
Keywords: Suites (Chamber orchestra); Orchestral music; Marches (Orchestra); Concerti grossi; concert; Suites; Preludes (Music); Marches (Music); Filmed performances; Internet videos